Transforming Industry through E-Commerce: Lessons from the COVID-19 Pandemic - Islam, Rabiul; Islam, Mohammad Fakhrul; Sultana, Sabina; Horaira, Gazi Abu; Islam, Md. Ariful (Journal of Cultural Analysis and Social Change, 2025)
The aim of this paper was to explore the 4.0 industrial revolution and globalization and their role in e-commerce as well as the current challenges facing e-commerce represented by the Coronavirus. The industry had gone through revolutions that contributed to its development, thus creating distinct and qualitative moves in it, and the matter had begun to shift from physical activity to mental creativity. Data for this study were obtained from existing literatures on industrial revolution of Coronavirus. The methodology heavily relied on existing previous literature on the subject being dealt with. The findings indicate that the economy has been affected and closely related to the results of the 4.0 industrial revolution, whether in a trade directly such as electronic commerce or by monitoring trade-related operations, analysing big data, and finding appropriate solutions. Moreover, the accomplishments achieved through them contributed significantly to increasing the benefit to people as the previous revolutions contributed at the time.